CONTINUITY INSIDE AL QURAN - Abdul Mannang; Mardan; Muhammad Yusuf (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Consistency, or consistency in truth, is wrong one concept important in teachings Islam which much mentioned in Al-Qur'an. Consistency considered as attitude hold on firm on road Which Correct in accordance with teachings Allah, despite facing various challenge. Study This aiming For analyze meaning And implementation steadfastness in The Quran and its relevance for life Muslim modern. With approach qualitative And method analysis interpretation thematic, This study found that that draft steadfastness No only demand consistency worship but Also demand steadfastness heart in various aspects of life, such as social, economic, and personal. The conclusion of this study states that istiqamah is a fundamental pillar that strengthens a person's piety and faith in interacting with Allah and fellow human beings.